Respuesta :

Answer:

Switch x and y, and solve for y

[tex]f^{-1}(x) =\frac{(x -4)^3}{8}[/tex]

Step-by-step explanation:

Given

[tex]f(x) = 3\sqrt{8x} + 4[/tex]

Required

Complete the steps to determine the inverse function

Solving (a): Complete the blanks

Switch x and y, and solve for y

Solving (b): Determine the inverse function

[tex]f(x) = \sqrt[3]{8x} + 4[/tex]

Replace f(x) with y

[tex]y = \sqrt[3]{8x} + 4[/tex]

Switch x and y

[tex]x = \sqrt[3]{8y} + 4[/tex]

Now, we solve for y

Subtract 4 from both sides

[tex]x -4= \sqrt[3]{8y} + 4-4[/tex]

[tex]x -4= \sqrt[3]{8y}[/tex]

Take cube roots of both sides

[tex](x -4)^3= 8y[/tex]

Divide both sides by 8

[tex]\frac{(x -4)^3}{8} = y[/tex]

So, we have:

[tex]y =\frac{(x -4)^3}{8}[/tex]

Hence, the inverse function is:

[tex]f^{-1}(x) =\frac{(x -4)^3}{8}[/tex]

Answer:

x

y

f^-1(x)= 1/8(x-4)^3 (plug in choices to match)

Step-by-step explanation:

You see, the guy above me already got it right. 1/8(x-4)^3 and (x-4)^3/8 are essentially the same thing. The only difference is either dividing by 8 and multiplying by 1/8, and that's only a visual difference.

ACCESS MORE